Young Consumer Behaviour
1 online resource (xx, 450 pages)
Keywords: "Although one perspective depicts young consumers as vulnerable and passive in the marketplace system, our knowledge of this consumer group will be inadequate if limited to this contention. Their roles and relevance in family consumption activities are becoming increasingly profound. Available evidence shows that they cannot be ignored in the marketplace dynamics as they consume goods and services in their households and are involved in various other active roles in their household consumption including making decisions where applicable. Hence, the landscape of young consumer behaviour is changing.Young Consumer Behaviour: A Research Companion focusses on exploring the behaviour of young consumers as individuals and societal members. The chapters address different aspects of consumption activities of children as individuals like motivation, involvement, perception, learning, attitude, the self, and personality. Similarly, chapters on consumer behaviour in social settings contextualised to young consumers including culture, sub-culture, family, and groups are incorporated into the book. This book fills a gap in the literature by addressing the dynamics of consumption patterns of this consumer group, in relation to various marketing stimuli and different stakeholders. It combines eclectic perspectives on the topic and specifically, bridges the gap between historical perspectives and contemporary issues.Building on the extant literature in the field of marketing and consumer behaviour, this book is a compendium of research materials and constitutes an essential reference source on young consumer behaviour issues with both academic and managerial implications."--Provided by publisher.